Pengaruh Teknologi Informasi dan Sistem Informasi Perpajakan Terhadap Kinerja Manajerial Keuangan - Myra Andriana; Tantiek Sumarlin; Roymon Panjaitan (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2020)
The company's financial managerial performance is heavily based on several factors in the decision making process. The factor analysis indicated on several factors independent variables are information technology and information systems of taxation. Both variables are the gauge of their influence on managerial performance in some manufacturing industries. This study was aimed to prove empirically the influence of information technology and information system on financial manager performance of manufacturing companies in Semarang district. The research data collection process through interview and questionnaire on with random data of 95 respondents with purposive sampling method. Analysis of data used with validity and reliability tests, testing using T test, F test and coefficient of determination. The results of this study showed there was a positive influence on information technology and information systems simultaneously based on the value of Adjusted R Square (R2) Information technology variables of 57% and the system variables of taxation information of 43% against performance Financial management in the manufacturing company.